1999
DOI: 10.1002/(sici)1099-0496(199911)28:5<321::aid-ppul3>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of oropharyngeal cultures in infants and young children with cystic fibrosis

Abstract: The objective of this study was to assess the diagnostic accuracy of oropharyngeal (OP) cultures relative to simultaneous bronchoalveolar lavage (BAL) cultures in very young children with CF, and to examine the effects of bacterial density, age, and study cohort on diagnostic accuracy. Respiratory culture data were analyzed from three independent, prospective studies involving simultaneous collection of 286 OP and BAL cultures from 141 children with CF <5 years of age. For predicting any growth of Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
255
2
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(278 citation statements)
references
References 15 publications
12
255
2
5
Order By: Relevance
“…This is approximately the rate reported in the US Cystic Fibrosis Foundation Data Registry in 1995 (34% at 5 yrs of age and 52% in 10 yr olds); however, in the US database, it is not specified what sample is assessed. In the study of ROSEN-FELD et al [25] the Pseudomonas spp. carrier rate is 31% at the age of 31±52 months.…”
Section: Discussionmentioning
confidence: 99%
“…This is approximately the rate reported in the US Cystic Fibrosis Foundation Data Registry in 1995 (34% at 5 yrs of age and 52% in 10 yr olds); however, in the US database, it is not specified what sample is assessed. In the study of ROSEN-FELD et al [25] the Pseudomonas spp. carrier rate is 31% at the age of 31±52 months.…”
Section: Discussionmentioning
confidence: 99%
“…Recentes instruções da Fundação Norte Americana de Fibrose Cística recomendam a necessidade de se usar o meio ágar sal manitol na rotina bacteriológica de espécimes de fibrocísticos (17) . Embora a cultura de espécimes faríngeos seja recomendada como uma alternativa à cultura para os fibrocísticos incapazes de fornecer escarro (17) , alguns estudos comparativos mostram que os espécimes faríngeos são inferiores ao escarro ou lavado bronco-alveolar no diagnóstico bacteriológico de infecções pulmonares naqueles pacientes (1,16) . No presente trabalho, a avaliação da acurácia das culturas de faringe não foi possível já que não se submeteu o mesmo participante, após a coleta do swab faríngeo, a controle pela realização de lavado bronco-alveolar.…”
Section: Discussionunclassified
“…The positive and negative predictive values of deep throat specimens or oropharyngeal specimens for the lower airway specimens have been studied with varying results, presumably due to the different patient populations and pathogens studied. 42 The yield of induced sputum relative to upper airway specimens has also been assessed in research settings, and induced sputum generally yields more potential pathogens. 43 The 2003 Infection Control Guideline for CF recommendations for processing all types of respiratory tract specimens (throat, sputum, or bronchoalveloar lavage) continues to be appropriate.…”
Section: Cf Ipandc Guideline Consensus: 100%mentioning
confidence: 99%
“…Specimens obtained from the upper airway lack sensitivity and specificity for the lower airway. 42 Despite standardized protocols for processing CF specimens, potential pathogens may escape detection due to low organism burden, overgrowth by other species, or misidentification. 1,447 Genotyping studies have also demonstrated the potential for replacement of an initial infecting Burkholderia strain with another strain (ie, superinfection) when CF patients have been segregated into groups on the basis of infection status.…”
Section: Ivf1 Cohort Segregation Versus All-patient Separationmentioning
confidence: 99%